Explanation:
remember, when multiplying 2 expressions, you need to multiply every term of one expressing with every term of the other expression and then add the individual results together (while observing their signs, of course).
so, e.g. 5(x - 4) = 5x - 5×4 = 5x - 20
therefore,
1)
5x - 20 = 2x + 10
5x - 2x = 10 + 20
3x = 30
x = 10
2)
-12s - 6 = 6s + 30
-12s - 6s = 30 + 6
-18s = 36
s = -2
3)
12c - 21 = -2c + 7
12c + 2c = 7 + 21
14c = 28
c = 2
4)
-10p + 30 = -10
-10p = -10 - 30
-10p = -40
p = 4
5)
8x = -2x - 20
8x + 2x = -20
10x = -20
x = -2
6)
21 + 6a - 5 - 2a = 8
4a + 16 = 8
4a = -8
a = -2